A reconstrução da vida no coração de um Deus sofredor : teologia e psicologia em diálogo para o cuidado integral no enlutamento - Costa, Ana Paula Reis da (2021)
Grief is a phenomenon that envolves around 4 million people per year in Brazil: people that suffer upon urgent demand of suport, wich also not always considers the and integrated care. This prevalence ends up composing a terrain vulnerable for life, with no social instrumentalization, intrinsically related to the experiences of Faith (not always contemplated in listening to bereavement, but present as a response to the rescue, preservation and recovery of life at grief). This research, therefore, makes use of clinical psychological material, given to theology, to understand what happens with the Faith and its implications in grief, and intends with empirical and theoretical methodological, qualitative, comparative and conclusively synthetic analysis, attend to the need of illuminate fundamental aspects in theology and psychology for effective and affective care amid forcible walk in the christian grief. As a basis, the research will be nourished essentially by the contributions to Jürgen Moltmann’s Theology of Hope and John Bowlby’s Psychology, as well as other related authors.